Mathematics Book Innovation Based on Digital Literature - Frisnoiry, Suci; Siregar, Tiur Malasari; Manurung, Sri Lestari (Journal of Education, Health and Sport, 2022)
The development of the era that makes the use of technology lively. Especially during the Covid-19 pandemic. All learning activities in schools are carried out online by utilizing various technologies. Therefore, a study was conducted with the aim of making a Mathematics Book based on Digital Literacy with multimedia assistance, namely Media Powtoon, Augmented Reality (AR) and the Kahoot application, in addition to seeing the feasibility of the book, the attractiveness of the book and the effectiveness of using Mathematics Books based on Digital Literacy in learning in high school N 1 Stabat. The research method used in this research is the development of the ADDIE model which has five stages of research implementation, namely Analysis, Design, Develop, Implement, and Evaluate. The result of this research has been the development of a digital-based Mathematics book with the title Geometry for SMA. This digital book has been through validation and testing. math book. In terms of feasibility, attractiveness and effectiveness. From the results of the validation to the two validators, it was obtained an assessment of "very feasible" meaning that digital books can be used and the results of the trial show that digital books are very interesting with the criteria of "Very Interesting" and are effective as seen from the results of the posttest calculations, digital books are very effective in increasing the score students who learn to use a digital book with the title Geometry for this high school.